2016
DOI: 10.1016/j.anifeedsci.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Growth, antioxidant capacity and muscle histochemistry of yellowtail kingfish (Seriola lalandi Valenciennes 1883): Selenium and temperature interaction

Abstract: The aim of this study was to investigate the interactive effects of temperature and dietary selenium concentrations on antioxidant capacity, muscle histochemistry and the growth, of juvenile yellowtail kingfish (Seriola lalandi). The yellowtail kingfish were exposed to two temperatures (21C or 26C) and three selenium levels (0.0, 2.0 or 4.0 mg Se kg −1 of feed) for 30 days. Final weight and specific growth rate (SGR) were significantly affected by water temperature (ρ<0.001) and dietary Se (ρ<0.001) suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 89 publications
0
11
0
Order By: Relevance
“…Despite the lack of effects on meagre growth performance, these results might indicate that Se is somehow preventing oxidation, as lipids are being stored in fish fed higher oil level (17%). Further studies need to be conducted in this matter, however, according to Ilham and Fotedar Se deficiency can lead to poor growth performance, lipid peroxidation and decreased GPx enzymatic activity in several fish species. Conversely, Se supplementation might prevent lipid peroxidation in fish tissues and contribute to better performance.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the lack of effects on meagre growth performance, these results might indicate that Se is somehow preventing oxidation, as lipids are being stored in fish fed higher oil level (17%). Further studies need to be conducted in this matter, however, according to Ilham and Fotedar Se deficiency can lead to poor growth performance, lipid peroxidation and decreased GPx enzymatic activity in several fish species. Conversely, Se supplementation might prevent lipid peroxidation in fish tissues and contribute to better performance.…”
Section: Resultsmentioning
confidence: 99%
“…coioides (Lin & Shiau, ), cobia Rachycentron canadum (Liu, Wang, Ai, Mai & Zhang, ), gibel carp Carassius auratus gibelio (Han et al., ), largemouth bass Micropterus salmoide (Zhu et al., ), and yellowtail kingfish S . lalandi (Ilham & Fotedar, ; Le & Fotedar, ). Moreover, our previous studies also suggested that an appropriate level of dietary Se was needed to support growth and antioxidant GPx activity of barramundi when fed with diets containing a high inclusion level of PP sources such as LM and SBM (Ilham, Siddik & Fotedar, ; Ilham, Fotedar & Munilkumar, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, if enzymatic activity is considered, the effect of Se is the opposite. Indeed, previous studies have reported that dietary supplementation of Se enhanced the antioxidant enzyme capacity in common carp ( Cyprinus carpio ) ( Elia et al, 2011 ), rainbow trout ( Oncorhynchus mykiss ) ( Küçükbay et al, 2009 ), cod ( Gadus morhua ) ( Penglase et al, 2010 ) and yellowtail kingfish ( Seriola lalandi ) ( Ilham & Fotedar, 2016 ). Based on gpx-1 and sod expression data obtained in our study, organic Se seemed to be the most efficient delivery form.…”
Section: Discussionmentioning
confidence: 99%